Arrays of Ag-nanoparticles decorated TiO2 nanotubes as reusable three-dimensional surface-enhanced Raman scattering substrates for molecule detection - Zhai, Haichao; Zhu, Chuhong; Wang, Xiujuan; Yuan, Yupeng; Tang, Haibin (Frontiers in Chemistry, 2022)
Three-dimensional surface-enhanced Raman scattering (SERS) substrates usually provide larger surface area and more hot spots in the excitation light beam, and thus higher sensitivity, when compared with the two-dimensional counterparts. Here a simple approach is presented for the fabrication of arrays of Ag-nanoparticles-decorated TiO2 nanotubes. Arrays of ZnO nanorods were fabricated in advance by a hydrothermal method. Then TiO2 nanotube arrays were achieved by immersing arrays of ZnO nanorods in an aqueous solution of (NH4)2TiF6. Vertically aligned TiO2 nanotube arrays were modified with dense Ag nanoparticles by Ag mirror reaction. High density of Ag nanoparticles decorated on TiO2 nanotubes provide plenty of hotspots for Raman enhancement. In addition, the fabricated array of Ag-nanoparticles-modified TiO2 nanotubes can serve as a reusable SERS substrate because the Ag nanoparticles/TiO2 nanotube hybrid possesses self-cleaning ability when illuminated by UV light. The sensitivity of the fabricated SERS substrate was investigated by the detection of organic dye molecules, and it was found that the limits of detection (LODs) of rhodamine 6G (R6G), malachite green (MG) and methylene blue (MB) were calculated to be 10-12 M, 10-9 M and 10-8 M, respectively. The enhancement factor (EF) of the three-dimensional SERS substrate was estimated to be as high as 1.4×108. Therefore, the prepared Ag-nanoparticles-modified TiO2 nanotube arrays have promising potentials to be applied to rapid and trace SERS detection of organic chemicals.